Fear of Missing Out Scale Indonesian Version: An Internal Structure Analysis - Wibaningrum, Gayatri; Aurellya, Ciptari Dhienda (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2020)
Fears of Missing Out (FOMO) is a form of anxiety that arises when someone uses social media. The FOMO scale has three components, namely Sense of Self/Self Esteem, Social Interaction/Extroversion, and Social Anxiety. The purpose of this study is to determine the number of dimensions that precisely measure the FOMO level of social media users. Factor analysis testing conducted on the FOMO Scale is exploratory factor analysis. Exploratory factor analysis is performed to determine the number of components that are most appropriate on the FOMO scale. This study involved 211 respondents who filled out the survey through Google Form. A total of 5 respondents were involved in the process of testing the Indonesian version of the FOMO scale measuring instrument and 2 respondents did not complete the demographic data. Therefore, 204 eligible respondents were used in the analysis process, namely undergraduate students and the frequency of social media checking in a day with an age range of 18-28 iyears. The results of the analysis show that the items on the Fear of Missing Out Scale are grouped into 3 components according to each component definitions.